The Role of EFL Teachers’ Praise and Love in Preventing Students’ Hopelessness - Liu, Fengzhen (Frontiers in Psychology, 2021)
The emotional dimension of language teaching and learning has recently gained momentum among researchers after pioneering works in positive psychology. Now, teachers’ and students’ emotions play an important role in learning process. Despite the growing body of research on many psychological constructs in L2 education, the role of teacher praise and love in precluding students’ sense of hopelessness about their future and efforts has been largely ignored. Motivated by this gap, the present study intended to review the definitions, conceptualizations, influencing factors, causes, and outcomes of these three psychological variables in EFL contexts. Moreover, to position the study, this article took a quick glance at the affective trend in education referring to positive outcomes of a loving pedagogy. Finally, different practical implications, research gaps, and future lines of research were provided for passionate researchers.